Sulfate and Chloride Resistance Properties of Portland Cement Blends - Morshed, Abu Zakir; Hashi, Suraiya; Biswas, Nitai; Sadik, Miftaul (Journal of Engineering Science, 2021)
About 53% area of Bangladesh is alluvial deposited and affected by sulfate, salinity and chloride in water and soil. Existing sulfate and chloride can severely damage the building in coastal regions. In this paper durability of cement is evaluated on the basis of strength of mortar cube, concrete cylinder test. Besides the sulfate resistance is measured by change of length of the mortar bar specimens during exposure to sulfate solution and the attacking chloride properties by Rapid chloride ion penetration test using OPC, PCC, 20% FA, 30% FA and 40% FA. The strength was observed in cube sample about 40.65, 37.2MPa after 13 weeks in sulfate solution and linear expansion was obtained about 0.28% and 0.133% for OPC and PCC cement with reference to the water. The compressive strength of the cylindrical specimens was about 16.96, 18.34 MPa for OPC and PCC, respectively at the age of 28 days. The permeability of chloride ion of OPC sample was 22.8% higher than the PCC at this age. Journal of Engineering Science 12(1), 2021, 69-75